Exploring new ways of regulation by resveratrol involving miRNAs, with emphasis on inflammation. (17th July 2015) - Latruffe, Norbert; Lançon, Allan; Frazzi, Raffaele; Aires, Virginie; Delmas, Dominique; Michaille, Jean‐Jacques; Djouadi, Fatima; Bastin, Jean; Cherkaoui‐Malki, Mustapha
Abstract : This review presents recent evidence implicating microRNAs (miRNAs) in the beneficial effects of resveratrol (trihydroxystilbene), a nonflavonoid plant polyphenol, with emphasis on its anti‐inflammatory effects. Many diseases and pathologies have been linked, directly or indirectly, to inflammation. These include infections, injuries, atherosclerosis, diabetes mellitus, obesity, cancer, osteoarthritis, age‐related macular degeneration, demyelination, and neurodegenerative diseases. Resveratrol can both decrease the secretion of proinflammatory cytokines (e.g., IL‐6, IL‐8, and TNF‐α) and increase the production of anti‐inflammatory cytokines; it also decreases the expression of adhesion proteins (e.g., ICAM‐1) and leukocyte chemoattractants (e.g., MCP‐1). Resveratrol's primary targets appear to be the transcription factors AP‐1 and NF‐κB, as well as the gene COX2 . Although no mechanistic link between any particular miRNA and resveratrol has been identified, resveratrol effects depend at least in part upon the modification of the expression of a variety of miRNAs that can be anti‐inflammatory (e.g., miR‐663), proinflammatory (e.g., miR‐155), tumor suppressing (e.g., miR‐663), or oncogenic (e.g., miR‐21).